2008
DOI: 10.1089/jwh.2008.0514
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Late in Life: A Hospital-Based Study of Birth Outcomes

Abstract: Pregnancy in older women is associated with adverse birth outcomes, particularly in primigravidas. Increased health promotion is required to highlight the risk of adverse birth outcomes in women who become pregnant for the first time in the late childbearing years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
13

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 32 publications
2
32
0
13
Order By: Relevance
“…A retrospective study carried out in Liverpool, Scotland, that included 9,506 records of births, observed a frequency of low birth weight in pregnant adolescent women and in pregnant late-age women, respectively, which found the presence of low birth weight in the extremes of reproductive life. (19) In an investigation of adolescent mothers, the rates of low-birth-weight deliveries increased consistently with younger maternal age. These rates were higher in newborns of mothers 15 years or younger.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study carried out in Liverpool, Scotland, that included 9,506 records of births, observed a frequency of low birth weight in pregnant adolescent women and in pregnant late-age women, respectively, which found the presence of low birth weight in the extremes of reproductive life. (19) In an investigation of adolescent mothers, the rates of low-birth-weight deliveries increased consistently with younger maternal age. These rates were higher in newborns of mothers 15 years or younger.…”
Section: Discussionmentioning
confidence: 99%
“…(8) In women with late gestation, more spontaneous and induced abortions have been seen, as well as increased risks for perinatal mortality, low vitality of the newborn, low birth weight, preterm delivery, and a small-for-gestational-age fetus. (9) Gestation of women with advanced maternal age has been considered a high risk factor, mainly for the growing incidence of hypertensive syndromes, premature rupture of membranes, diabetes, and a higher risk for a five-minute Apgar score of less than seven. (10) This study analyzed and compared perinatal results of pregnancy in adolescent women and in women between 20 and 34 years old from data collected from a Live Born Information System.…”
Section: Introductionmentioning
confidence: 99%
“…1,[6][7][8][9][12][13][14] No entanto, a perceção das mães em relação a uma gravidez tardia é pouco conhecida. 3,[13][14][15] Nos quatro meses em que decorreu este estudo verificou-se que 32,2% (n = 237) do total de nascimentos foram de mães com idade igual ou superior a 35 anos, o que está de acordo não só com o que se verificou no total de nascimentos do ano de 2015 no mesmo hospital (32%), 5 mas também a nível nacional.…”
Section: Discussionunclassified
“…1,[6][7][8][9][12][13][14] Tal como descrito na literatura, verificou-se de forma estatisticamente significativa que as mulheres IMA já tinham tido um maior número de abortos espontâneos. Verificou-se ainda um maior número de cesarianas neste grupo, tal como referido em estudos anteriores.…”
Section: Discussionunclassified
“…14,17,19 Early booking, close supervision in the antenatal and intrapartum period, appropriately timed obstetric intervention and the advocation of active management of labour may have contributed to good fetal outcome. 9 Obstetric practice presently has moved away from high cavity forceps delivery and unwarranted breech extraction.…”
Section: Perinatal Mortality and Morbiditymentioning
confidence: 99%